Green chemical mechanical polishing of sapphire wafers using a novel slurry. Issue 44 (30th September 2020) - Xie, Wenxiang; Zhang, Zhenyu; Liao, Longxing; Liu, Jie; Su, Hongjiu; Wang, Shudong; Guo, Dongming
Abstract : Toxic and corrosive solutions are widely used in the preparation of abrasives and chemical mechanical polishing (CMP) of sapphire wafers, resulting in potential environmental pollution. Abstract : Toxic and corrosive solutions are widely used in the preparation of abrasives and chemical mechanical polishing (CMP) of sapphire wafers, resulting in potential environmental pollution. Developing a novel green CMP technique to achieve light-emitting diode sapphire wafers is a significant challenge. In this study, a novel green CMP slurry, consisting of silica, sorbitol, aminomethyl propanol, and deionized water was developed for sapphire wafers. After CMP, the sapphire wafers were cleaned with deionized water and dried with compressed air, which is a green process. After CMP, the surface roughness R a of the sapphire wafer surface with an area of 5 × 5 μm 2 was 0.098 nm, which is the lowest surface roughness reported to date for sapphire wafers. Tetrahydroxy-coordinated Al(OH)4 − ions were produced in the alkaline CMP slurry, and chelation occurred between sorbitol and these ions. The proposed green CMP has potential applications in the semiconductor and microelectronics industries.